Assessing the Impact of Shoreline Changes on Framework Adaptive Tourism Development (Case Study: Mandiri Beach, Pesisir Barat, Lampung) - Fahmi Aziz; Sahid Sahid; Nana Putri Yanto; Surya Tri Esthi Wira Hutama; Trika Agnestasia Tarigan; Asep Nurul Ajiid Mustofa; Rahmatullah Harianja; Muhammad Alfazri; Nur Zaida Almanti (JURNAL GEOGRAFI, 2026)
This study investigates shoreline changes at Mandiri Beach, Pesisir Barat Regency, Lampung Province, during the period 2013–2024 using the Digital Shoreline Analysis System (DSAS). Landsat imagery was processed through Google Earth Engine (GEE) and ArcGIS, with the Modified Normalized Difference Water Index (MNDWI) applied to delineate land–water boundaries. Shoreline dynamics were quantified using DSAS metrics, including Net Shoreline Movement (NSM) and End Point Rate (EPR). The results reveal significant spatial variability: several segments experienced erosion, particularly in western and northeastern zones, while other areas showed accretion, mainly across gently sloping beaches and river mouths. In the primary research area, abrasion reached a maximum of 1.49 m with an average NSM of 1.41 m, and the End Point Rate indicated a gradual annual abrasion trend of 0.13 m/year. Meanwhile, Mandiri Sejati District exhibited more extreme changes, with maximum accretion of 11.84 m and maximum abrasion of 16.2 m, reflecting high sensitivity to environmental and anthropogenic pressures. These findings highlight the importance of adaptive coastal management framework to mitigate erosion risks and optimise accretion zones for sustainable tourism development. The study contributes to disaster mitigation planning, coastal resource management, and the integration of ecological conservation with tourism utilisation.